Black outfit negatively impacts psychological factors of tennis players in tropical environment - Robin, N.; Carien, R.; Dominique, L.; Ruart, S. (Movement & Sport Sciences - Science & Motricité, 2025)
Many tennis tournaments take place in hot and humid environments in which players practice outdoors in conditions of high temperatures and solar radiation. The objective of this original study was to test the influence of the color of clothing on psychological factors (e.g., rating of perceived exertion, affects, feeling of fatigue, of sweat and thermal and comfort perception) and physiological variables (e.g., skin, tympanic and clothing temperatures). Thirteen skilled tennis players completed two 75-minute match sessions, in hot (M=31.4°C WBGT) and humid (M=78% rH) conditions, wearing white then black outfits counterbalanced. The results of this study showed an increase in the tympanic temperature the first 30 minutes of effort whatever the color as well as higher clothing temperatures when wearing black clothes. Moreover, the perception of effort, the feelings of fatigue and heat, as well as the discomfort of the players increased with the duration of exercise. Finally, from 60 minutes of play, the players perceived the effort as more difficult, had greater discomfort and felt less good in black clothes than in white clothes. We recommend that tennis players wear white or light-coloured clothing in a hot and humid environment because the color black can negatively impacts psychological factors.